News and views on public finances: A survey experiment - Jan Behringer; Lena Dräger; Sebastian Dullien; Sebastian Gechert (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2024)
We use novel German survey data to investigate how perceptions and information about public finances influence attitudes towards public debt and fiscal rules. On average, people strongly underestimate the debt-to-GDP ratio, overestimate the interest-to-tax-revenue ratio and favor a tighter German debt brake. In an information treatment experiment, people consider public debt to be a more (less) severe problem once they learn the actual debt-to-GDP or interest-to-tax-revenue ratio is higher (lower) than their estimates. However, the treatment effects partly vanish when anchoring respondents' beliefs with historical public debt figures. We find no treatment effects on attitudes towards the debt brake.
Keywords: D83; E60; H31; H60; 330; public debt; fiscal rules; information treatment; expectations